A retrospective propensity score-matched analysis of oncological and functional outcomes of submental island flap versus radial forearm free flap for oral cavity cancer reconstruction - Pichit Sittitrai; Donyarat Ruenmarkkaew; Chananchida Kumkun; Chonticha Srivanitchapoom (BMC, 2024)
Abstract Background This retrospective study aims to compare the oncological and functional outcomes of the submental island flap versus the radial forearm free flap used for oral cavity cancer reconstruction after minimizing differences in baseline characteristics. Methods Propensity scores for each oral cavity cancer patient who underwent surgical resection and immediate reconstruction with a submental island flap or a radial forearm free flap with a flap size ≤ 60 cm2 between October 2008 and December 2021 were generated based on the likelihood of being selected given their baseline characteristics. Patients were matched using a 1:1 nearest-neighbor approach. Results The final matched-pair analysis included 51 patients in each group. The 5-year overall survival, disease-specific survival, and locoregional control rates were 70.1% and 64.8% (p = 0.612), 77.3% and 83.7% (p = 0.857), and 76.1% and 73.3% (p = 0.664), respectively, for the submental island flap group and the radial forearm free flap group. Speech and swallowing functions were comparable between groups. However, there were significantly lower rates of complication associated with both donor and recipient sites in the submental island flap group, and also the duration of hospital stays and hospital costs were significantly lower in these patients. A subgroup analysis of patients in which the reconstruction was carried out using the submental island flap procedure revealed that in selected cases, the presence of clinically and pathologically positive level I lymph nodes did not affect survival or locoregional control rates. Conclusions Although this study was not randomized, the matched-pair analysis of surgically treated oral cavity cancer patients showed that submental island flap reconstruction is as effective as radial forearm free flap reconstruction with regard to oncological and functional outcomes with lower complication rates, hospital stay, and hospital costs. This flap can be safely and effectively performed in selected cases with a clinical level I lymph node smaller than 1.5 cm and no signs of extranodal extension.